Arthrodesis using Iliac Crest autograft in revision surgery of the first metatarsophalangeal joint total arthroplasty for the treatment of Hallux Rigidus: a retrospective study - Ahmet Yurteri; Numan Mercan; Ahmet Fevzi Kekeç; Ahmet Yıldırım (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Purpose The treatments for hallux rigidus (HR) encompass a wide spectrum, including conservative methods and surgical approaches such as arthroplasty and arthrodesis. This study aims to evaluate the outcomes of revision with arthrodesis following the failure of the first metatarsophalangeal joint total arthroplasty (MTPJ1TA). Materials and methods Patients who had surgery at two advanced orthopedic centers between January 1, 2020, and January 1, 2024, were reviewed. Those with at least 6 months of postoperative follow-up were assessed for demographics (gender, age, side), reoperation rates, complications, Visual Analogue Scale (VAS) scores, Foot and Ankle Disability Index (FADI) scores, and American Orthopaedic Foot and Ankle Society Hallux Metatarsophalangeal and Interphalangeal Scale (AOFAS-HMI) scores. Radiological evaluations included hallux valgus angle (HVA), intermetatarsal angle (IMA), dorsiflexion angle (DFA), and first ray length (FRL) in anteroposterior and lateral views. Results Of 27 patients, 4 were male (15%) and 23 female (85%), with an average age of 56.18 ± 7.49 years (range 41–72). Arthrodesis was performed in 26 patients, with one requiring reoperation due to implant failure. Average VAS scores were 7.14 preoperatively and 3.55 postoperatively (p < 0.05). Average FADI scores were 50.51 preoperatively and 71.51 postoperatively (p < 0.05). Average AOFAS-HMI scores were 51.22 preoperatively and 70.59 postoperatively (p < 0.05). Average HVA was 19.7° preoperatively and 6.29° postoperatively (p < 0.05). Average IMA was 10.66° preoperatively and 11.37° postoperatively (p = 0.406). Average DFA was 34.14° preoperatively and 22.33° postoperatively (p < 0.05). Average anteroposterior FRL was 10.17 cm preoperatively and 10.77 cm postoperatively (p < 0.05). Average lateral FRL was 10.12 cm preoperatively and 10.42 cm postoperatively (p < 0.05). None of the patients in the study exhibited postoperative donor site complications or transfer metatarsalgia, while a 100% rate of bone union was observed. Conclusion We think that revision of MTPJ1TA with arthrodesis is a safe treatment option. Additionally, the use of an iliac crest autograft can be a viable option to restore bone stock and create a biological environment conducive to fusion. This study evaluates revision surgery with arthrodesis in the largest patient group with failed MTPJ1TA, highlighting its significance in the field. However, further studies are needed to determine the ideal surgical procedure.